Patient preferences for first-line treatment of classical Hodgkin lymphoma: a US survey and discrete choice experiment. Issue 11 (18th September 2020) - Khan, Niloufer; Feliciano, Joseph; Müller, Kerstin; He, Mary; Tao, Rei; Korol, Ellen; Dalal, Mehul; Rebeira, Mayvis; Matasar, Matthew
Abstract: A cross-sectional online survey, including a discrete choice experiment (DCE), was used to investigate first-line treatment preferences in patients with classical Hodgkin lymphoma (cHL) in the United States; 141 patients (median age 35.0 years) participated. In the DCE, risk of progression at 2 years (progression free survival) had the highest relative importance to patients (31.3%) when considering first-line treatments, followed by 2-year overall survival (OS; 26.9%), on-treatment pulmonary toxicity (23.3%), and on-treatment peripheral neuropathy (18.5%). Marginal rate of substitution analyses demonstrated that a 0.44% and 0.09% increase in 2-year OS was required for patients to accept a 1% increase in the risk of disease progression at 2 years and peripheral neuropathy, respectively. A 2.6% increase in 2-year OS was needed to accept a 7% rather than a 2% risk of pulmonary toxicity. In summary, patients with cHL rated survival attributes as more important than drug-related toxicity when considering first-line treatments.